PENGARUH EDUKASI TENTANG ANEMIA TERHADAP PENGETAHUAN DAN SIKAP KONSUMSI TABLET TAMBAH DARAH IBU HAMIL - Andi Fatwa Tenri Awaru; Rahmaniah (Bina Generasi : Jurnal Kesehatan, 2025)
Anemia that occurs during pregnancy can affect both maternal health and fetal development. While the incidence of anemia in pregnant women in Indonesia is still quite high. One of the efforts to prevent anemia is the consumption of blood supplement tablets in pregnant women, but the coverage of blood supplement tablets consumption is still low among pregnant women. This study aims to determine the effect of education about anemia on the knowledge and attitudes of pregnant women on the consumption of blood tablets. The study was a quasi experimental study with a one group pre post without control group design to determine the effect of education about anemia and blood supplement tablets on the knowledge and attitudes of pregnant women in consuming blood supplement tablets before and after being given education. The sample of this study were all pregnant women who came to the posyandu of the Banggae II Health Center working area. Sampling was done using non-probability sampling technique and met the inclusion and exclusion criteria. Respondents who participated in this study were 20 pregnant women. The tools used in this study were questionnaires containing the identity of respondents, questions to measure knowledge as many as 10 questions with correct and incorrect answer options, and questions to assess the attitudes of pregnant women related to compliance with blood supplementation tablet consumption as many as 10 questions with yes and no answer options. The results showed an increase in knowledge from 7.90 to 9.45 with a p-value for the paired t-test of 0.022 (p<0.05). Meanwhile, the average pre and post-test scores on attitude assessment also showed an increase from 7.90 to 8.80 with a p-value of 0.002 (p<0.05). These results indicate that education has a significant effect on both increasing knowledge and changing attitudes in pregnant women.